2018
DOI: 10.1002/app.46390
|View full text |Cite
|
Sign up to set email alerts
|

Alginate and alginate/hyaluronic acid membranes generated by electrospinning in wet conditions: Relationship between solution viscosity and spinnability

Abstract: The methodology to create alginate and alginate/hyaluronic acid membranes, which involves wet conditions electrospinning, is presented in this paper. The wet conditions allow simultaneously to work in water solutions avoiding the toxic solvents and to obtain crosslinked alginate. An accurate rheological characterization of all solutions examined is performed. By optimizing the electrospinning parameters, it is possible to obtain alginate membranes with homogeneous nanofibers and a narrow diameter distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…On the other hand, these systems require complex, costly, and time-consuming fabrications methods that can hardly be applied on a very large area. To this end, polymers promise to reduce fabrication costs and simplify processes while allowing for the easy obtainment of square meter scale structures [4][5][6]. Actually, large area and industrial fabrications have already been reported for colloidal opals that are made of self-assembled microspheres [7] and for multilayered distributed Bragg reflectors (DBRs) [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, these systems require complex, costly, and time-consuming fabrications methods that can hardly be applied on a very large area. To this end, polymers promise to reduce fabrication costs and simplify processes while allowing for the easy obtainment of square meter scale structures [4][5][6]. Actually, large area and industrial fabrications have already been reported for colloidal opals that are made of self-assembled microspheres [7] and for multilayered distributed Bragg reflectors (DBRs) [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…An integral part of semisolids development is a comprehensive rheological study of model bases, which allows concluding about the effect of excipients on the structural and mechanical parameters of a formulation, on which biopharmaceutical and consumer properties depend, as well as to rationally select the technological parameters of the manufacturing process [19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…The modification of the collector in order to facilitate the fabrication of the electrospun nanofibrous alginate was also reported [19,40,55,56]. In this regard, the electrically grounded collector is immersed in bi/multivalent ion aqueous solution for simultaneous crosslinking of the collected alginate nanofibers.…”
Section: Advanced Electrospinning Techniquesmentioning
confidence: 99%